1995
DOI: 10.1080/00039896.1995.9935980
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Neurologic Sequelae to Cholinesterase Inhibition among Agricultural Pesticide Applicators

Abstract: To test the hypothesis that chronic neurologic sequelae are associated with cholinesterase depression short of frank organophosphate poisoning, we compared 45 male subjects who had a history of moderate cholinesterase inhibition with 90 male subjects who had neither past cholinesterase inhibition nor current pesticide exposure. Cholinesterase-inhibited subjects were defined as having had a history of (a) red blood cell cholinesterase at 70% or less of baseline or (b) plasma cholinesterase at 60% or less of bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 12 publications
3
65
2
4
Order By: Relevance
“…Most of these studies did not exclude individuals with a history of pesticide poisoning. Several studies in which such individuals were excluded found no relationship of chronic exposure to neurobehavioral performance or nerve conduction velocity (Ames et al 1995;Engel et al 1998;Fiedler et al 1997), but other studies of nonpoisoned individuals have found associations (Stephens et al 1995;van Wendel de Joode et al 2001). We found that farm work was related to worse performance even after excluding 19 individuals who had experienced acute toxic reactions to pesticides.…”
Section: Discussioncontrasting
confidence: 53%
“…Most of these studies did not exclude individuals with a history of pesticide poisoning. Several studies in which such individuals were excluded found no relationship of chronic exposure to neurobehavioral performance or nerve conduction velocity (Ames et al 1995;Engel et al 1998;Fiedler et al 1997), but other studies of nonpoisoned individuals have found associations (Stephens et al 1995;van Wendel de Joode et al 2001). We found that farm work was related to worse performance even after excluding 19 individuals who had experienced acute toxic reactions to pesticides.…”
Section: Discussioncontrasting
confidence: 53%
“…Most studies found deficits on one or several tests of cognitive function, but not on other tests, and there was not full agreement among studies in which tests were affected. Further, no deficits in cognitive function were found in other studies of OP exposure (10,76,108,269).…”
Section: Chronic Low-level Exposurementioning
confidence: 55%
“…It is suggested in the present study that Delsen may exert their effects by inhibiting cholinesterase enzymes, as in Delsen users median SCV was significantly correlated with serum cholinesterase activities, which was lower than the activities in controls. By contrast, it has been observed that slowing of peripheral nerve conduction velocities were not related to cholinesterase inhibition in organophosphate or carbamate users 41) .…”
Section: Discussionmentioning
confidence: 90%